2019
DOI: 10.1101/846493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatocytic Prominin-1 protects against liver fibrosis by stabilizing the SMAD7 protein

Abstract: Background and Aims:Prominin-1 (PROM1) is known to be upregulated in hepatocytic progenitor cells (HPCs) and cholangiocytes of fibrotic livers. To understand the function of upregulated PROM1 during liver fibrosis, we analyzed liver fibrosis from global and liverspecific Prom1 knockout mice and investigated the molecular mechanism of how Prom1 protects the liver against liver fibrosis. Methods:We analyzed PROM1 expression from human liver with mild and severe liver fibrosis (n=4-9). Liver fibrosis was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…PROM1 is well known as a marker for cancer stem cells and normal stem cells. Recent studies have revealed its ability to regulate various cellular signal transduction pathways by interacting with PI3K, HDAC6, radixin, and SMAD7 [15,16,21,22]. Here, we demonstrated that PROM1 is also necessary for regulating IL-6 signaling during liver regeneration.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…PROM1 is well known as a marker for cancer stem cells and normal stem cells. Recent studies have revealed its ability to regulate various cellular signal transduction pathways by interacting with PI3K, HDAC6, radixin, and SMAD7 [15,16,21,22]. Here, we demonstrated that PROM1 is also necessary for regulating IL-6 signaling during liver regeneration.…”
Section: Discussionmentioning
confidence: 53%
“…Because hepatocellular PROM1 upregulation is also observed after bile duct ligation (BDL) [16] and a lithogenic diet (data not shown), various liver damages might lead to hepatocellular PROM1 upregulation. Many extracellular and intracellular factors, such as HIF-1, TGF1, p53 and mTOR, regulate the expression of PROM1 [12,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diamond surface stimulated the overexpression of several potential oncogenes, such as NUP37, USP17L10, PROM1, MACROH2A1 and LAMTOR1. 79,[98][99][100][101] Overexpression of the nuclear pore structural protein NUP37 in the context of research by Luo et al 98 indicates growth promotion of HepG2 cancer cells by altering signal transduction to the nucleus. Studies on another protein, USP17, have shown that deubiquitination with its participation is a process necessary for the progression of the cell cycle and the G1/S phase transition of cancer cells.…”
Section: Dovepressmentioning
confidence: 99%